COMMUNITY BEHAVIOR IN THE UTILIZATION OF MANGROVE FOREST (Case: Belawan Sicanang Village, Medan Belawan District, Medan City) - Lia Kristin Saragih (Agripreneur : Jurnal Pertanian Agribisnis, 2020)
This study aims to analyze the behavior of the community in the use of mangrove forests, to determine the value of the community's WTP (Willingness to Pay) on the existence of mangrove forests, and to analyze the influence of community behavior on the willingness to pay (Willingness to Pay) of the community. Determining the research area by purposive sampling and to take samples using the non-probability sampling method. In analyzing the data, the researcher used descriptive analysis and logistic regression methods. The results showed that the behavior of the community in Sicanang Village towards the existence of mangrove forests, in terms of the knowledge, attitudes, and actions of the people carried out was classified in the good category. The value of the community's WTP (Willingness to Pay) for the existence of mangrove forests varies in the range of Rp. 2,000 – Rp. 10,000, with the average value of WTP (Willingness to Pay) of the community of Rp. 3,375. Overall, the behavior of the community on the existence of mangrove forests has a significant effect on willingness to pay (Willingness to Pay), but partially the knowledge and attitudes of the community have no significant effect.